Novelty in Content Creation: Experimental Results Using Deep Learning–Based Image Recognition on a Large Social Network - Huang, Justin; Kaul, Rupali; Narayanan, Sridhar (Marketing Science, 2026)
Using a field experiment on a social network and machine learning methods, we investigate whether artists create more novel content after getting attention and recognition.